(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
One of the most important tasks of higher educational institutions is the training of specialists to be able to adapt to changes in their professional life. At the end of the twentieth and the beginning of the 21st centuries, some methods for developing foreign language competence, needed for their future professional activity, were created by teachers. However, the effectiveness of these methods has not been studied. This fact has aroused the authors’ interest and generated the idea about the necessity to conduct scientific research in order to identify the most effective methods of teaching foreign languages for special purposes. Methods: The given research paper is based on the analysis of Russian and foreign scholars’ scientific works covering the problem of teaching foreign languages for special purposes to the students of humanitarian professions, as well as on the basis of the results from questioning students of bachelor degree programs who study foreign languages for special purposes in the field of humanitarian professions, and also of the results from questioning teachers specializing in teaching foreign languages for special purposes. Results: In the students’ opinion, the most effective methods of teaching foreign languages for special purposes in the field of humanitarian professions are the following: discussion, ICT (information and communication technologies), and SCRUM (framework that helps teams work together, encourages team to learn through on a problem). According to the interviewed teachers’ opinion, the most effective methods are discussion, ICT, and round table. The “dilemma” method is the least effective according to the students. As for the teachers, the less effective method is CLIL (content and language integrated learning).